Experimental and numerical investigation of interactions between above and below ground drainage systems. - Djordjević, Slobodan (Water Science and Technology)
This paper presents the results of the experimental and numerical investigation of interactions between surface flood flow in urban areas and the flow in below ground drainage systems (sewer pipes and manholes). An experimental rig has been set up at the Water Engineering Laboratory at the University of Sheffield. It consists of a full scale gully structure with inlet grating, which connects the 8 m2 surface area with the pipe underneath that can function as an outfall and is also further connected to a tank so that it can come under surcharging conditions and cause outflow from the gully. A three-dimensional CFD (Computational Fluid Dynamics) model has been set up to investigate the hydraulic performance of this type of gully inlet during the interactions between surface flood flow and surcharged pipe flow. Preliminary results show that the numerical model can replicate various complex 3D flow features observed in laboratory conditions. This agreement is overall better in the case of water entering the gully than for the outflow conditions. The influence of the surface transverse slope on flow characteristics has been demonstrated. It is shown that re-circulation zones can form downstream from the gully. The number and size of these zones is influenced by the transverse terrain slope.